Characterization of the complete chloroplast genome of orchid family species Cymbidium bicolor (Orchidaceae) - Guojia Hu; Huijuan Zhou; Shuonxin Zhang; Peng Zhao (Mitochondrial DNA. Part B. Resources, 2020)
Cymbidium bicolor belongs to Orchid family (Orchidaceae), it has high ornamental and traditional medicinal value. The complete chloroplast genome of C. bicolor was sequenced using the Illumina Hiseq platform. The size of the C. bicolor chloroplast genome is 156,528 bp, with an average GC content of 36.8%. This chloroplast genome has containing a large single copy (LSC) region of 85,907 bp, a small single copy (SSC) region of 17,215 bp, and two inverted (IRa and IRb) repeat regions of two 26,703 bp. A total of 124 genes were annotated, including 78 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. A maximum likelihood phylogenetic tree indicated that C. bicolor is closely related to C. mannii in the genus Cymbidium based on 16 whole chloroplast genome sequences.